Autolysis in Crustacean Tissues after Death: A Case Study Using the Procambarus clarkii Hepatopancreas. (13th January 2021) - Huang, Xiaoli; Xiong, Guanqing; Chen, Xia; Liu, Ruisi; Li, Minghao; Ji, Lili; Zhang, Xiaoli; Geng, Yi; Ou, Yangping; Chen, Defang; Yin, Lizi; Li, Liangyu; et al.
Abstract : Autolysis is an internal phenomenon following the death of an organism that leads to the degradation of tissues. In order to explore the initial stages of autolysis and attempt to establish reference standards for tissue changes after death, we studied the rapidly autolyzing tissue of the crayfish hepatopancreas. Samples from the hepatopancreas of crayfish were examined 0, 5, 10, 30, 60, and 120 minutes after death. Histological and ultrapathological examinations and evaluations and apoptotic cell counts were conducted to determine the initiation time and degree of autolysis. The results showed that autolysis in the hepatopancreas of crayfish began within 5 minutes. Initially, autolysis manifested in the swelling of hepatic tubular cells and the widening of mesenchyme. Cells undergoing autolysis showed severe organelle necrolysis. Based on these observations, tissue samples should be collected and preserved within five minutes to avoid interfering with histopathological diagnoses.